Menopause and Hormone Therapy - Yasmin, Nahid; Sultana, Sayeeda; Habib, Shahin Akhter Jahan (Bangladesh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: Menopause is a natural biological process, not a medical illness. Although it is associated with hormonal, physical and psychosocial changes in life, it is not the end of youth or of sexuality. Several generations ago, few women lived beyond menopause, Today, women may spend as much as half of their life after menopause. Hormone therapy (HT) has been widely used in recent decades to relieve the signs and symptoms of menopause and - doctors thought- to prevent disease associated with aging. However, new long term evidence has demonstrated that hormone therapy may actually increase risk of serious health conditions, such as heart disease , breast cancer and stroke. Oestrogen therapy is still a safe, short -term option for some women, but numerous other therapies also are available to help women manage menopausal symptoms and stay healthy during this important phase of life. DOI: 10.3329/bmj.v36i2.3612 Bangladesh Medical Journal 36(2) 2007 48-51